Are surgeons and anesthesiologists lying to each other or gaming the system? A national random sample survey about "truth-telling practices" in the perioperative setting in the United States. Issue 1 (December 2015) - Nurok, Michael; Lee, Yuo-yu; Ma, Yan; Kirwan, Anthony; Wynia, Matthew; Segal, Scott
Abstract Background The perioperative setting demands strong teamwork to ensure safe patient care, but anecdotally surgeons and anesthesiologists are not always fully truthful with each other. The present study sought to determine the frequency of misrepresentation of the truth in the perioperative setting. Methods Direct mailed survey in the United States about misrepresenting information to colleagues in a national random sample of 1130 anesthesiologists and 1130 surgeons. Results Reflecting the sensitive nature of these questions, only 252 (11 %) surveys were returned-128/1130 by anesthesiologists and 124/1130 by surgeons. While modest numbers of both anesthesiologists (34/128, 27 %) and surgeons (8/124, 7 %) acknowledged misreporting information at least once per month, misreporting was considerably more common among responding anesthesiologists. Among anesthesiologists the majority (68 %) were concerned that surgeons misreported information to them once a month or more often, though only 8 % of surgeons shared reciprocal concerns. More than a third of responding anesthesiologists (36 %) reported having seen their teachers misreport information to surgeons during their training. Conclusions These findings, though preliminary due to the small sample, raise concerns about a possible culture of misrepresentation, passed on between generations, in some perioperative environments. Misreporting of information should be examined in more detail and addressed at local levels whenever it is found. Further research is required to determine if the reported behaviors represent routine gaming of perioperative care systems or deliberate and intentional deception. Strategies aimed at fostering conditions in which open honest communication can thrive should be investigated.